Dimensions of green office evidence from regency/city government offices in Central Java, Indonesia - Yusepaldo Pasharibu; Agus Sugiarto; Tutuk Ariarsanti; Petrus Wijayant (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Green office that is implemented within the environmental management system is one of the current concerns of environmentally friendly advocates. It is to do with the phenomenon of high environmental degradation and the low awareness of people about environmental-friendly behavior. Previous studies have indicated that the application of green office, particularly in government agencies, had not been optimally practiced due to low commitment and scant discussions. This study was thus conducted with the aim of exploring and identifying the various applications and dimensions of the green office concept among government institutions in Central Java, Indonesia. To fulfil the research objectives, a triangulation research method was employed, comprising focus group discussions, in-depth interviews and close observations of the offices located in five (5) municipal government agencies. Results indicated that seven green office dimensions were applied by the government institutions, namely: energy conservation, water conservation, building layouts, office technology, human resource management, work systems, and office waste management.
Keywords: M0; O3; 650; green office; e-office; eco-office; office governance; green office dimensions; environmentally friendly